PERSEPSI KONSUMEN YANG BERBELANJA KOMODITI PERTANIAN PADA SUPERMARKET DI KOTA MANADO - Deliana ., Bihuku; Grace Adonia Josefina Rumagit; Caroline B. D. Pakasi (Sam Ratulangi University, 2018)
This research aims to describe consumer perceptions based on the attributes of ease in shopping, product, price, situation, and service to agricultural commodities consumers shopping at Supermarket in Manado City. The data collected were analyzed descriptively and presented in tabular form and cross tabulation. The study was conducted for three months from October 2017 until December 2017 in three supermarkets namely Multimart Manado, Hypermart Mantos, and Transmart Carrefour. The data used is the primary data obtained through interviews to 90 respondents who have been shopping for agricultural commodities in Supermarket in October 2017. The results of research showed that the perception of consumers who shop for agricultural commodities in supermarkets in Manado City against the five attributes that influence it, including in the category strongly agrre (54.7 %), agree (41.8 %), neutral (3.5 %), while categories disagree and strongly disagree was not selected. Of the categories strongly agree, product attributes ranks first (60.4 %), followed by the situation attributes (57.4 %), service attributes (56.3 %), ease of shopping attributes (50.7 %), and final position price attributes (48.9 %).